TECHNOLOGY OF DEVELOPMENT OF WELLS USING COILED TUBING INSTALLATIONS - Femiak, Ya. М.; Vytyaz, О. Y.; Femiak, V. Ya.; Fedyk, О. M. (НТУ "Дніпровська політехніка", 2024)
The basis of coiled tubing technologies is the use of a flexible metal pipe, which is wound on a drum and lowered and raised from the well by a special unit (Fig. 1: a, b). The mobility of coiled tubing installations makes it possible to effectively use them in remote deposits, especially marine ones, to develop an individual scheme of repair, development, and maintenance for each well. Many companies in the world develop and manufacture coiled tubing equipment. The products of each of them have their advantages and disadvantages. Among the most famous companies are «Halliburton», «Schlumberger», «B. J. Services», and many others.